2017
DOI: 10.1002/2016jc012416
|View full text |Cite
|
Sign up to set email alerts
|

Wind‐driven ocean dynamics impact on the contrasting sea‐ice trends around West Antarctica

Abstract: Since late 1978, Antarctic sea‐ice extent in the East Pacific has retreated persistently over the Amundsen and Bellingshausen Seas in warm seasons, but expanded over the Ross and Amundsen Seas in cold seasons, while almost opposite seasonal trends have occurred in the Atlantic over the Weddell Sea. By using a surface‐forced ocean and sea‐ice coupled model, we show that regional wind‐driven ocean dynamics played a key role in driving these trends. In the East Pacific, the strengthening Southern Hemisphere (SH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 78 publications
(126 reference statements)
0
11
1
Order By: Relevance
“…This sex‐specific response supports our predictions about more pelagic females and is consistent with Weimerskirch et al () who found that shifts in meridional winds primarily affected foraging performance of female wandering albatross Diomedea exulans . However, the inverse relationship between zonal winds and male NGP survival is contrary to our predictions and may therefore indicate other indirect effects, such as wind‐driven changes in oceanographic conditions (Holland & Kwok, ; Lee et al, ).…”
Section: Discussioncontrasting
confidence: 99%
“…This sex‐specific response supports our predictions about more pelagic females and is consistent with Weimerskirch et al () who found that shifts in meridional winds primarily affected foraging performance of female wandering albatross Diomedea exulans . However, the inverse relationship between zonal winds and male NGP survival is contrary to our predictions and may therefore indicate other indirect effects, such as wind‐driven changes in oceanographic conditions (Holland & Kwok, ; Lee et al, ).…”
Section: Discussioncontrasting
confidence: 99%
“…4 ), leading to strong annual mean trends and a clear feedback signature. In other sectors, the trends over 1979–2013 vary between seasons, leading to smaller trends in annual average, and suggesting that other processes with out-of-phase impacts across seasons are dominant 29 . Furthermore, the insignificant positive correlations from 0 to 50 m in the Bellingshausen–Amundsen sector in observations (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a strengthening of westerlies at ~60S and related enhanced northward Ekman transport (Fig. 5f) are likely to facilitate sea ice expansion during cold seasons 54 .…”
Section: Connections With Tropical Internal Variabilitymentioning
confidence: 99%